Public Participation in Local Governance: A Case Study of Development Planning in East Jakarta Administration - Fahmi, Ade; Sa’adih, Sa’adih; Hutauruk, Rosinta Paulina (Universitas Sang Bumi Ruwa Jurai, 2022)
This study examines the dynamics of public participation in local governance through the case of development planning mechanisms in East Jakarta Administration. Using a qualitative case study approach, the research analyzes the implementation of Musyawarah Perencanaan Pembangunan (Musrenbang) as a platform for community involvement in decision-making. Findings reveal that although formal channels for participation exist, challenges persist in terms of inclusiveness, feedback responsiveness, and continuity of involvement beyond consultation stages. The study highlights the importance of institutional support, civic education, and participatory culture in strengthening citizen engagement.